Intravenous Leiomyomatosis Complicated by Arteriovenous Fistula: Case Series and Literature Review - Kan, Haoxuan; Cao, Yang; Chen, Yuexin; Zheng, Yuehong (Frontiers in Cardiovascular Medicine, 2022)
Background: Uterine intravenous leiomyomatosis (IVL), a rare type of uterine leiomyoma is defined by intravascular proliferation of a histologically benign smooth muscle cell tumor. Pelvic arterio-venous fistula (AVF) is a rare vascular malformation that is most commonly congenital, post traumatic or iatrogenic. The link between leiomyomatosis and arteriovenous fistula has received little attention in the medical literature. Results: We provide a case series of seven patients, four of whom were from our center, who had IVL complicated by a pelvic arterio-venous fistula (AVF). The symptoms of right heart failure were noted as swelling in the abdomen and two legs, as well as a significant amount of ascites. Coil embolization of AVFs may be beneficial in minimizing bleeding during IVL surgery. A review of all accessible literature published on IVLs from 2000 to 2020 was conducted, and data was retrieved from 78 papers totaling 262 cases. Complications and recurrence were associated with pelvic mass excision and intravascular remnant tumor, respectively. Conclusion: IVL combined with AVF aggravates congestion symptoms of surrounding organs. It is worth noting the uncommon combination of AVF and IVL, stressing the importance of a thorough assessment and surgical approach in IVL treatment.